Personality and Satisfaction by Vital Areas in Psychology from public university students from Lima - Velásquez C., Carlos (2016)
The objective of the present study is to investigate the possible relationship between personality styles and satisfaction by vital areas in students of psychology of a public University in Lima. Took a sample of 417 students, 182 men and 235 women, applied the scale of satisfaction by vital areas (SAV) and the exploratory personality questionnaire (CEPER III). Negative associations between the SAV scale and CEPER III personality styles were detected. But if there were multiple positive correlations, in the style Histrionic,narcissistic and obsessive compulsive with satisfaction in vital areas.